THE ROLE OF PARENTS IN SELF-HELP SKILLS FOR PHYSICAL MOTOR DEVELOPMENT OF CHILDREN - Maryam, Nesa Hasbi; Fairuzillah, Muhammad Naufal; Khan, Muhammad Nasir (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2025)
This study aimed to explore the role of parents in developing children's self-help skills and how different parenting styles affect their physical motor development. This research used a library research method to explore the role of parents in self-help skills and their impact on children's physical motor development. Self-help skills are a crucial aspect of the physical motor development of early childhood, encompassing activities such as eating, dressing, using household tools, and using the toilet, which require fine and gross motor coordination. Parents play a crucial role in developing these skills through different parenting styles: permissive, authoritarian, and democratic. Parents play a crucial role by modeling usage and guiding children in daily practices, thereby enhancing their comfort and responsibility in maintaining personal hygiene. Active parental involvement is essential for helping children develop self-help skills and achieve optimal physical motor development. Appropriate parenting styles and consistent guidance lay a strong foundation for children to become independent, confident, and capable individuals, effectively navigating life's challenges.